Czy to zadziała? O wsparciu społecznym online osób cierpiących na choroby przewlekłe - Mencel, Paulina (Studia Edukacyjne, 2022)
Today, the more and more common chronic diseases among women are classified as critical life events, and increase the need to seek social support. Their frequency and such changes that have occurred in society as increased need for online support, show that the topic requires further empirical research. The article presents the unique features of chronic diseases and the role of holistic social support. The most important information on the opportunities and risks of online support for chronically ill women has been collected. Due to its importance and universality, there is a need to develop this issue and apply more scientific research to it.